Add-on effect of the Guizhi Fuling formula for management of reduced fertility potential in women with polycystic ovary syndrome: A systematic review and meta-analysis of randomized controlled trials - Rong, Anna; Ta, Na; E., Lihua; Meng, Wenbin (Frontiers in Endocrinology, 2023)
Background Guizhi Fuling (GZFL) pill, a traditional Chinese herbal formula including Semen Persicae, Ramulus Cinnamomi, Poria, Radix Paeoniae Alba, and Cortex Moutan, has been widely applied in the management of gynecological diseases. Objective To evaluate the add-on effect of the GZFL formula for treating reduced fertility potential in women with polycystic ovary syndrome (PCOS) by conducting a systematic review and meta-analysis. Methods Two reviewers independently searched the PubMed, Embase, Cochrane Library, Wanfang, SinoMed, and CKNI databases until 09/11/2022. Eligible studies were randomized controlled trials (RCTs) of the GZFL formula plus Western medicine versus the Western medicine for treating PCOS. The primary endpoint was the ovulation, pregnancy, and miscarriage rate. The secondary endpoints included the serum follicle-stimulating hormone (FSH), total testosterone, luteinizing hormone (LH), estradiol, and homeostasis model assessment insulin resistance (HOMA-IR). Results There were 16 RCTs with 1,385 patients identified. The GZFL formula plus Western medicine significantly improved the ovulation rate (risk ratios [RR] 1.24; 95% confidence intervals [CI] 1.15–1.34) and pregnancy rate (RR 1.53; 95% CI 1.38 to 1.69) than the Western medicine alone. Adjuvant treatment with the GZFL formula also significantly decreased the serum FSH (mean difference [MD] -0.48 U/l; 95% CI -0.80 to -0.15), total testosterone (standard mean difference [SMD] -1.07; 95% CI -1.71 to -0.44), LH level (MD -2.19 U/l; 95% CI -3.04 to -1.34), and HOMA-IR (MD -0.47; 95% CI -0.60 to -0.34). However, there was no significant difference in the miscarriage rate (RR 0.89; 95% CI 0.36–2.20) and serum estradiol level (SMD 0.34; 95% CI -0.25 to 0.94) between two groups. Conclusions The GZFL formula as adjuvant therapy can improve the ovulation and pregnancy rates in women with PCOS. Its beneficial effects may correlate with reducing FSH, total testosterone, and LH and ameliorating insulin resistance. However, more well-designed RCTs with larger samples and multicenter trials are required to confirm the current findings due to uncertainty of the evidence. Systematic review registration PROSPERO identifier, CRD42022354530.